Respuesta :
For this case we have the following polynomial:
[tex] x^2 + 5x - 6 = 0 [/tex]
The quadratic formula is given by:
[tex] x = \frac{-b +/- \sqrt{b^2 - 4ac}}{2a} [/tex]
Substituting values in the given equation we have:
[tex] x = \frac{-5 +/- \sqrt{5^2 - 4(1)(-6)}}{2(1)} [/tex]
Rewriting we have:
[tex] x = \frac{-5 +/- \sqrt{25 + 24}}{2} [/tex]
[tex] x = \frac{-5 +/- \sqrt{49}}{2} [/tex]
[tex] x = \frac{-5 +/- 7}{2} [/tex]
Therefore, the solutions are given by:
Solution 1:
[tex]x=\frac{-5+7}{2}=\frac{2}{2}=1[/tex]
Solution 2:
[tex]x=\frac{-5-7}{2} =-\frac{12}{2}=-6[/tex]
Answer:
the solutions to the equation are:
x = –6, 1